2022
DOI: 10.1177/22925503221088841
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Retrieval of Lacerated Flexor Tendons: A Scoping Review

Abstract: Introduction: Flexor tendon laceration is often followed by retraction of the proximal stump. The goals of this review were to describe the myriad of proximal stump retrieval surgical techniques and where available to provide the clinical evidence associated with each. Methods: A Medline and Web of Science search was performed to identify any publication whose primary purpose was to describe a tendon retrieval technique. The techniques were assigned to 8 groups. Clinical outcomes, where reported, and advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…In zone II flexor tendon injury, retrieval of retracted proximal tendon stump can be problematic due to the presence of the relatively inelastic tendon sheath; trauma created during retrieval can lead to poor functional outcome and needs to be minimized. A plethora of tendon retrieval methods were published in literature ( 1 , 11 ). Agreed with the current evidence, in this study, most respondents (85%) supported atraumatic tendon retrieval, and reported a variety of retrieval techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In zone II flexor tendon injury, retrieval of retracted proximal tendon stump can be problematic due to the presence of the relatively inelastic tendon sheath; trauma created during retrieval can lead to poor functional outcome and needs to be minimized. A plethora of tendon retrieval methods were published in literature ( 1 , 11 ). Agreed with the current evidence, in this study, most respondents (85%) supported atraumatic tendon retrieval, and reported a variety of retrieval techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Most respondents (45%) mentioned the use of sutures and a flexible feeding tube, and some respondents (10%) also mentioned the creation of an extra incision. However, a number of the respondents (15%) still chose “Milking” in which the proximal tendon stump was milked down through the tendon sheath despite its low success rate (61%) ( 11 ). Supported by 10% of the respondents, looped sutures were able to retrieve the proximal stump through tendon sheath without the need of a feeding tube ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation